Akibat Hukum atas Pencantuman Nomor Orang Lain sebagai Kontak Darurat Secara Sepihak dalam Pengajuan Pinjaman Online - Putri Pinasti; Putri Mufidah; Putri Ni'matul Maula; Selvin Armynova; Aqiila Banyu Valentara; Achmad Faidzuddin; Dwi Aryanti Ramadhani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The absence of legal force if the data is provided due to oversight or obtained by force and/or fraud which makes the agreement invalid according to Article 1321 of the Civil Code. This research contains the legal consequences if the agreement made between the borrower and the online loan service provider cannot involve a third party or the owner of the emergency contact. This research uses empirical juridical research methods, which specifically investigate how the law is enacted/practiced in society in relation to actual or real events to collect the necessary facts and data, after the data is collected then identify the problem which ultimately leads to problem solving. Data collection methods are carried out through literature study and qualitative descriptive analysis with a statutory approach. Third parties who feel aggrieved due to acts of abuse committed by loan recipients and online loan organizers of online money lending agreements can file a lawsuit for both material and immaterial damages. In the event of harm, the owner of the emergency contact is entitled to legal protection by imposing civil sanctions, administrative sanctions, and criminal sanctions on violators of the misuse of personal data.The use of personal data must comply with the law and respect the privacy rights of individuals. Inclusion of emergency contact numbers must be based on the valid consent of the data owner. The inclusion of emergency contact numbers without the consent of the owner is a violation that can have legal consequences. The legal consequences for violations of this personal data must be considered by these violators in order to provide a deterrent effect.